Implementation of Social-Emotional Competence Based on the CASEL Framework: A Systematic Literature Review - Rahayu, Ni Putu Widhi Linda; Redhana, I Wayan (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aims to analyze the implementation of Social Emotional Competencies (SEC) strategies across educational levels and examine the role of teachers in managing emotionally intelligent classrooms. This research employed a Systematic Literature Review (SLR) following the PRISMA guidelines. Articles were selected based on inclusion criteria, including empirical studies published between 2019 and 2026 that discussed the implementation of SEC or Social Emotional Learning (SEL) in educational settings and highlighted teachers’ roles in learning and classroom management. Ten articles met the eligibility criteria and were included in the review. The findings indicate that the integration of the CASEL framework through active learning approaches, such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), and differentiated learning, contributes positively to students’ well-being, engagement, and academic achievement. The review also reveals that teachers with strong social-emotional competencies are better able to create inclusive, supportive, and conducive learning environments. However, challenges remain, including limited instructional time, heavy administrative workloads, and insufficient professional training related to SEC implementation. Therefore, strengthening teachers’ social-emotional competencies through continuous professional development programs is recommended to support more holistic and student-centered learning practices.